Art‐Based Action Research for Art Education in the North. (21st August 2019) - Jokela, Timo
Abstract: This article introduces the art‐based action research (ABAR) methodology as part of the international discussion of art‐based educational research (ABER). The participatory and dialogical approach of ABAR was inspired by a consideration of the pressure for change in art education stemming from the practices of relational and dialogical contemporary art. The need for ABAR as a tool of culturally decolonising, sustainable art education research was identified in multidisciplinary collaboration with the University of Lapland's (UoL) northern and circumpolar network. The methodology was developed collaboratively by a group of art educators and researchers at UoL to support the artist/teacher/researcher with professional skills for seeking solutions to recognised problems and to promote future actions and aspirations in the changing North and Arctic. This article describes how ABAR has been used in school projects, in doctoral theses and finally in a development project with an impact on regional development in the North. These examples show how art education developed through the ABAR method has supported decolonisation, revitalisation and cultural sustainability in schools, communities and businesses.